Deletion of genes involved in glutamate metabolism to improve poly-gamma-glutamic acid production in B. amyloliquefaciens LL3. (1st February 2015) - Zhang, Wei; He, Yulian; Gao, Weixia; Feng, Jun; Cao, Mingfeng; Yang, Chao; Song, Cunjiang; Wang, Shufang
Abstract: Here, we attempted to elevate poly-gamma-glutamic acid (γ-PGA) production by modifying genes involved in glutamate metabolism in Bacillus amyloliquefaciens LL3. Products of rocR, rocG and gudB facilitate the conversion from glutamate to 2-oxoglutarate in Bacillus subtillis . The gene odhA is responsible for the synthesis of a component of the 2-oxoglutarate dehydrogenase complex that catalyzes the oxidative decarboxylation of 2-oxoglutarate to succinyl coenzyme A. In-frame deletions of these four genes were performed. In shake flask experiments the gudB / rocG double mutant presented enhanced production of γ-PGA, a 38 % increase compared with wild type. When fermented in a 5-L fermenter with pH control, the γ-PGA yield of the rocR mutant was increased to 5.83 g/L from 4.55 g/L for shake flask experiments. The gudB/rocG double mutant produced 5.68 g/L γ-PGA compared with that of 4.03 g/L for the wild type, a 40 % increase. Those results indicated the possibility of improving γ-PGA production by modifying glutamate metabolism, and identified potential genetic targets to improve γ-PGA production.